Acute Neurologic Disorder from an Inhibitor of Fatty Acid Amide Hydrolase - Kerbrat, Anne; Ferré, Jean-Christophe; Fillatre, Pierre; Ronzière, Thomas; Vannier, Stéphane; Carsin-Nicol, Béatrice; Lavoué, Sylvain; Vérin, Marc; Gauvrit, Jean-Yves; Le Tulzo, Yves; Edan, Gilles (The New England journal of medicine, 2016)
Three patients had severe ataxia and memory impairment in a phase 1 trial of a fatty acid amide hydrolase inhibitor designed as an analgesic and antiinflammatory drug. One patient became brain dead. MRI of the brain showed lesions in the pons and hippocampi. A decrease in fatty acid amide hydrolase (FAAH) activity increases the levels of endogenous analogues of cannabinoids, or endocannabinoids. 1 FAAH inhibitors have shown analgesic and antiinflammatory activity in animal models, 2 and some have been tested for these purposes in phase 1 and phase 2 studies. 3 Phase 3 studies were not pursued owing to a lack of efficacy. BIA 10-2474, with the chemical name 3-(1-(cyclohexyl(methyl)carbamoyl)-1H-imidazol-4-yl)pyridine 1-oxide, is a new reversible FAAH inhibitor. A phase 1 study was conducted in healthy volunteers to explore the safety profile of BIA 10-2474. Five of the six participants who had received the highest cumulative dose . . .